Highly Selective Pd Nanosheet Aerogel Catalyst with Hybrid Strain Induced by Laser Irradiation and P Doping Postprocess. Issue 4 (27th November 2022) - Zhang, Ran; Zhao, Yan; Guo, Ziang; Liu, Xuan; Zhu, Liye; Jiang, Yijian
Abstract: Strain engineering of electrocatalysts provides an effective strategy to improve the intrinsic catalytic activity. Here, the defect‐rich crystalline/amorphous Pd nanosheet aerogel with hybrid microstrain and lattice strain is synthesized by combining laser irradiation and phosphorus doping methods. The surface strain exhibited by the microstrain and lattice strain shifts the d‐band center of the electrocatalyst, enhancing the adsorption of intermediates in the ethanol oxidation reaction and thus improving the catalytic performances. The measured mass activity, specific activity and C1‐path selectivity of the Pd nanosheet aerogel are 4.48, 3.06, and 5.06 times higher than those of commercial Pd/C, respectively. These findings afford a new strategy for the preparation of highl activity and C1 pathway selective catalysts and provide insight into the catalytic mechanism of strain‐rich heterojunction materials based on tunable surface strain values. Abstract : The defect‐rich crystalline/amorphous Pd nanosheet aerogel with hybrid microstrain and lattice strain is synthesized by combining laser irradiation in liquid and phosphorus doping methods. The measured mass activity, specific activity, and C1‐path selectivity of the Pd nanosheet aerogel were 4.48, 3.06, and 5.06 times higher than those of commercial Pd/C, respectively.